Awareness Regarding Diabetes Mellitus and Its’ Complications in Type 2 Diabetic Patients - Thabit, Maral F (AL-Kindy College Medical Journal, 2013)
Background: Various studies conducted in many parts of the world suggest that there is lack of public awareness and knowledge of various aspects related to diabetes. With proper education, awareness, earlier detection and better care, many complications and co-morbidities can be reduced in diabetic population.Objectives: to evaluate the level of awareness of diabetes mellitus type 2 patients regarding their disease and its’ complications.Methods: Cross – sectional survey was conducted during November and December 2011, in the Medical centers of Al Baladiat, Mustansyria and Zuafranya, including 145 type 2 diabetic patients (58.6 % males, 41.4% females) who were subjected to self–structured questionnaires regarding different aspects of the disease Results: Medical staff was the main source of information in 75% of patients, poor proportion of correct responses (25.5%) regarding disease etiology, symptomatology of feeling hungry (42.7%), generalized weakness (33.1%) also (44.8% & 30.1%) knew about the target blood sugar and blood pressure respectively. The proportions of correct responses regarding disease complications were not acceptable especially for myocardial infarction (18.6%), also poor daily blood sugar monitoring (11.03%). The knowledge of patients regarding management of disease by life style modifications was poor regarding physical exercise (40.6%) and weight reduction (40%) and (46.8%) of patients knew their drugs name , doses and side effects.Conclusions: Generally, poor awareness of patients regarding diabetes mellitus and its complications